LEVEL OF ESTROGEN HORMONE AND ESTRUS PERFORMANCE OF DIFFERENT POSTPARTUM ESTRUS OF JAWA RANDU GOAT - Tanjung, A. D.; Setiatin, E. T.; Samsudewa, D. (Diponegoro University, 2015)
The purpose of this research was to determine the reproductive quality of normal compared withabnormal postpartum estrus (PPE) of Jawa Randu Goats (n = 16 goats) on estrogen hormon level andestrus profile. Total samples were 16 Jawa Randu goats. The data were analyzed descriptively and nonparametric data were analyzed using Mann Whitney U-test of Statistical Package for the Social science(SPSS) 16. Descriptive statistics was used on estrogen hormone and resulting that normal postpartumestrus (PPE) Jawa Randu Goats had a better level (133.8; 141.5; 155.6; 162.25; 167.75 pg/mL)compared with abnormal postpartum estrus of Jawa Randu Goat (109.9; 111.35; 101.2; 132.2; 142.45pg/mL). Mann Whitney U-test used for the abundance of cervical mucus and ferning showed nonsignificantly different of postpartum estrus between both groups. Jawa Randu goats with normal PPEhad a higher estrogen level than abnormal PPE goats. However, for the abundance and ferning ofcervical mucus, between the two groups of goats was not different.